1998
DOI: 10.1111/j.1540-8175.1998.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Transesophageal Stress Echocardiography

Abstract: Exercise echocardiography is a widely used modality for the noninvasive assessment of coronary artery disease. However, limitations exist inherent to the acquisition of transthoracic echocardiographic images. Although transesophageal echocardiography has been used during pacing or pharmacological stress, its use during exercise stress testing has not been clinically feasible due to the large probe size. Recently, a miniaturized transesophageal probe was developed, and we sought to test the feasibility of using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Several studies reported the feasibility and accuracy of ICE using a miniaturized 10 Fr, monoplane, probe (AcuNav/Acuson/Siemens) to guide transcatheter PFO closure 13–15 . This miniaturized probe has been used previously during conventional TEE, 7 and the nasal approach by means of both the AcuNav catheter and a prototype TEE probe has also been utilized for the purpose 8–12 . Prompted by the above studies, we felt that the AcuNav transducer inserted via the nose could have been used profitably to guide transcatheter closure of PFO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported the feasibility and accuracy of ICE using a miniaturized 10 Fr, monoplane, probe (AcuNav/Acuson/Siemens) to guide transcatheter PFO closure 13–15 . This miniaturized probe has been used previously during conventional TEE, 7 and the nasal approach by means of both the AcuNav catheter and a prototype TEE probe has also been utilized for the purpose 8–12 . Prompted by the above studies, we felt that the AcuNav transducer inserted via the nose could have been used profitably to guide transcatheter closure of PFO.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] This miniaturized probe has been used previously during conventional TEE, 7 and the nasal approach by means of both the AcuNav catheter and a prototype TEE probe has also been utilized for the purpose. [8][9][10][11][12] Prompted by the above studies, we felt that the AcuNav transducer inserted via the nose could have been used profitably to guide transcatheter closure of PFO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-rate pacing is a valid stress test to be used in conjunction with echocardiography; it is independent of physical exercise and does not require drug administration[ 1 ]. Its evolution in the last 20 years started from an invasive (intravenous) right atrial pacing modality, combined with a ionising imaging technique such as radionuclide ventriculography; it moved to a seminvasive modality combined with 2D echo, using transnasal[ 2 ] or transoral catheter for transesophageal [ 3 - 8 ] left atrial pacing; and finally evolved to a totally noninvasive modality with external programming in patients with permanent pacemaker for right atrial or ventricular pacing [ 1 , 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%